SECOND PATHWAYS IN THE PATHOPHYSIOLOGYOF ISCHEMIC PRIAPISM AND TREATMENTALTERNATIVES - Karakeci, A.; Firdolas, F.; Ozan, T.; Unus, I; Ogras, M. S.; Orhan, I (Wiley-Blackwell, 2014)
[Abstract Not Available]